Brain function abnormalities and inflammation in HIV-positive men who have sex with men with depressive disorders - Yang Zhang; Yang Zhang; Yihui He; Yihui He; Yuan Fang; Yuan Fang; Miaotian Cai; Guangqiang Sun; Guangqiang Sun; Rui Wang; Rui Wang; Jiaxin Zhen; et al. (Frontiers in Psychiatry)
BackgroundDepressive disorders are highly prevalent among people with HIV (PWH) and are related to aberrant inflammation and immune responses. However, there is currently a lack of investigation into the neurological, inflammatory, endocrine, and immune aspects of HIV-associated depressive disorders (HADD).MethodsThe study involved 33 HIV-positive men who have sex with men with depressive disorders (HADD group) and 47 without neuropsychiatric disorders (HIV control group). Participants underwent resting-state functional magnetic resonance imaging (rs-fMRI) scans and assessments of peripheral blood. Peripheral blood cytokines, plasma concentrations of hormone and neurotrophic factors, and immune cell levels were determined using liquid chip, enzyme-linked immunosorbent assay, and flow cytometry, respectively. The correlation of imaging alterations with clinical variables and peripheral blood indicators was assessed.ResultsCompared to the HIV control group, the HADD group exhibited a higher fractional amplitude of low-frequency fluctuations in the left superior parietal gyrus, lower regional homogeneity in the left precentral gyrus, and reduced voxel-wise functional connectivity for the seed region in the right precentral gyrus with clusters in the right cuneus, etc. Furthermore, the HADD group had higher levels of interferon-gamma, a higher frequency of non-classical monocytes, and higher expression levels of perforin and CD38 on specific cells. These imaging results were significantly correlated with peripheral blood indicators and clinical variables.ConclusionThis rs-fMRI study provides considerable evidence for abnormal intrinsic brain activity in people with HADD. Furthermore, our data also indicate the detrimental effects of depression-related inflammation on PWH. Therefore, it is imperative to increase attention to HADD and implement effective preventive interventions accordingly.